ขบวนการแรงงานกับการเปลี่ยนผ่านสู่ประชาธิปไตยในสาธารณรัฐแห่งสหภาพเมียนมา, ค.ศ. 1988-2018 - ณัฐพล ตันตระกูลทรัพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
This research seeks to understand the process of democratic transition in Myanmar and its impact on the labor movement, particularly during the years 1988-2018. The key questions this study explores are: What is the role of the labor movement in Myanmar’s transition to democracy? and How has the labor movement changed throughout this period of transition? The factors, conditions, and procedures that shape the labor movement will be analyzed through the use of case studies to observe the ongoing democratic transition process in Myanmar as a whole. The data collection for this research was conducted by use of qualitative methods, including survey of documents, news, related laws, and other academic works. Additionally, in-depth interviews were conducted with 16 key informants to further understand phenomena, examine the data, and establish concrete links.The author utilized the Protest Event Analysis (PEA) method to analyze the labor movement in order to interpret the data and develop the arguments. The findings indicated that while the Myanmar labor movement was reformed during the period of study, it has not had a significant effect on the current process of democratic transition. The labor movement is likely to be under the control of the state, referred to as a "Coopted labor movement", which limits its ability to push for change. However, the movement can play a role in policymaking process as an institutional structure that is created by the state, which remains an important channel providing the opportunity to claim and protect labor rights. Such a feature of the labor movement also reflects the characteristics of Myanmar civil society as well, as Myanmar civil society has resurrected during the democratic transition period, but it is in a relatively limited, depoliticized role and does not impact power relations in the political structure.